STUDY OF EMULSION PRODUCTS STABILIZED WITH SURFACTANTS BASED ON RHAMNOLIPIDS PSEUDOMONAS SP. PS-17 - I. R., PELEKH-BONDARUK; R. I., VILDANOVA; L. I., KOBYLINSKA; Y. Y., BILA; S. B., BILOUS (International Journal of Applied Pharmaceutics, 2022)
Objective: To study the effectiveness of the biocomplex of surfactants based on rhamnolipids Pseudomonas sp. PS-17 (biocomplex PS) as an emulsifier in emulsions for use in dermatology. Methods: Technological methods of o/w emulsions manufacturing, ultrasonic dispersion, as well as microscopic studies of manufactured emulsions have been used. Results: To select the concentration of biocomplex PS as an emulsifier, studies of the emulsifying properties of bio complex PS in comparison with polysorbate 80 have been performed, taking into account the similarity of the hydrophilic-lipophilic balance of these substances. Several compositions of emulsions have been studied in which the biocomplex PS has been used as an independent emulsifier in a concentration from 4 to 10%, as well as in combination with other emulsifiers-lanolin and glycerol monostearate. Conclusion: The creation of stable o/w emulsions requires the use of high concentrations of biocomplex PS as an emulsifier, more than 10%, which is impractical and economically unreasonable. The use of biocomplex PS as a co-emulsifier with emulsifiers of the second type allows obtaining stable emulsions at a total concentration of complex emulsifier 7-10%.